Slip behavior of stud connectors of steel-concrete composite beams in the whole process of fatigue loading. (October 2022) - Liang, Xiuyu; Yi, Xiyan; Wang, Bing; Liu, Xiaoling
Abstract: The slip between steel-concrete composite beams will affect structural overall performance. It is necessary to master the slip degradation rule of stud connectors in their service life. Eleven push-out specimens of stud connectors were designed and fabricated to perform static, fatigue, and residual slip tests. The slip growth and distribution characteristics of stud connectors during the full process under fatigue and static load were analyzed. An improved stud load-slip model, considering ultimate slip, was established under monotonic loading, based on statistical data and the literature. Considering the cumulative increase in stud connector slip and degradation of bearing capacity due to fatigue damage, a load-slip calculation model for the full process of studs under any number of fatigue load cycles was established and verified by test values. Finally, the influence of key parameters in stud connector slip was discussed. Results showed that stud slip can be divided into cumulative slip during fatigue loading and residual slip after fatigue loading. During fatigue loading, stud cumulative slip increased in three stages of "fast-slow-rapid, " accounting for 10, 80, and 10% of fatigue life, respectively. After fatigue loading, residual and total stud slip decreased with increased fatigue cycles, which indicated that overall stud deformation performance gradually deteriorated due to increased fatigue damage. Calculated values from the proposed full-process load-slip model for studs were in good agreement with experimental results. Parameter analysis showed that total stud slip increased with increased upper limit of fatigue load and stud diameter.